The notion of stylistic marking in language units (general and theoretical aspects) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2018)
The article investigates various approaches of studying the notion of “stylistic marking”. In particular, it notes that the phenomenon of stylistic marking in modern linguistics is understood in different ways. Some researchers consider it in terms of the notion of linguistic norm; the others associate this notion with stylistic values and the presence of various connotations in the language unit. It should be mentiond that modern stylistics actively uses the term “stylistic coloring”, which usually refers to the correlation of the language unit with a certain functional language style. In addition, some researchers define the stylistic coloring as the presence of additional semantics and stylistic shades in words. This article interprets stylistic marking (stylistic coloring) as the presence in the language units additional connotative emotional, expressive, evaluative or stylistic information, which predetermines the ability of this unit to create a certain stylistic effect. Such language units provides in speech different shades depending on communicative and pragmatic intentions of the speaker (for example, solemnity, high style, inofficial speaking, familiarity, irony, humor, comic style, rudeness, aggressiveness, etc.).
Keywords: stylistic marking; stylistic coloring; stylistic meaning; connotation